Liquidity Ratio Analysis in Measuring Company Financial Health at PT. Indofood CBP Sukses Makmur Tbk. - Damayanti, DHea Aulia; Darma Taujiharrahman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The liquidity ratio will be used to assess PT. Indofood CBP Sukses Makmur Tbk's ability to meet its obligations to pay short-term debt. The current ratio, quick ratio, cash ratio, and inventory to net working capital ratios will be used to analyze PT. Indofood CBP Sukses Makmur Tbk's ability to pay short-term debt. The purpose of this study was to determine the liquidity quality of PT. Indofood CBP Sukses Makmur Tbk during 2015 to 2019 as a form of analysis of the company's fundamental health. The approach used in this study is a qualitative descriptive analysis method from a financial standpoint, reporting data from PT. Indofood CBP Success Makmur. Tbk. from 2015 to 2019. The data showed that PT. Indofood CBP Success Makmur. Tbk. had a very good liquidity ratio from 2015 to 2019. With a current ratio of 233 percent, a quick ratio of 183 percent, a cash ratio of 116 percent, and an inventory to net working capital ratio of 43 percent, the company is in good shape.